Impacts of household income on beef at-home consumption: Evidence from urban China - Wen-bo ZHU; Yong-fu CHEN; Jing ZHAO; Bei-bei WU (Journal of Integrative Agriculture, 2021)
Beef consumption in China has increased substantially from 5.0 million tons in 2000 to 7.7 million tons in 2019 thanks to rapid income growth, but still remains low compared to pork and poultry consumption. Improving the understanding about the impacts of household income on beef consumption in China is necessary to forecast future beef demand and inform the domestic beef industry, especially in the context of unprecedented expansion of middle income class in China. Based on survey data of 32 878 urban households collected by the National Bureau of Statistics of China, we employed the inverse hyperbolic sine (IHS) double-hurdle model to estimate income elasticities of beef demand across different income groups and simulated possible trends of future beef consumption of Chinese urban residents. The empirical results showed that the unconditional income elasticities of beef consumption at home vary between 0.169 for the low-income group and 0.671 for the high-income group. The simulated results indicated that beef consumption is expected to increase by 12.0 to 38.8% in 10 years and by 18.6 to 70.5% in 15 years under distinct income growth scenarios. Our findings provide practical insights for policy makers and other stakeholders about future beef demand, such as potential opportunities embedded in rising beef demand for domestic producers and world beef exporters as well as the urgency of improving the supply chain resilience of beef in China.